Artificial Photosynthesis for Sustainable Fuel and Chemical Production. Issue 11 (15th January 2015) - Kim, Dohyung; Sakimoto, Kelsey K.; Hong, Dachao; Yang, Peidong
Abstract The apparent incongruity between the increasing consumption of fuels and chemicals and the finite amount of resources has led us to seek means to maintain the sustainability of our society. Artificial photosynthesis, which utilizes sunlight to create high‐value chemicals from abundant resources, is considered as the most promising and viable method. This Minireview describes the progress and challenges in the field of artificial photosynthesis in terms of its key components: developments in photoelectrochemical water splitting and recent progress in electrochemical CO2 reduction. Advances in catalysis, concerning the use of renewable hydrogen as a feedstock for major chemical production, are outlined to shed light on the ultimate role of artificial photosynthesis in achieving sustainable chemistry.